Totalitarian and Authoritarian Regimes in Europe. Legacies and Lessons from the Twentieth Century. Ed. by J. W. Borejsza and K. Ziemer in Cooperation with M. Hułas, 2006 - Zmierczak, Maria (Czasopismo Prawno-Historyczne, 2007)
Recenzja: Totalitarian and Authoritarian Regimes in Europe. Legacies and Lessons from the Twentieth Century, ed. by Jerzy W. Borejsza and Klaus Ziemer in Cooperation with Magdalena Hulas, Berghahn Books, New York, Oxford, Instytut Historyczny PAN, Niemiecki Instytut Historyczny, 2006, ss. XIV + 607, indeks osób.